Coincidence or Psi? The Epistemic Import of Spontaneous Cases of Purported Psi Identified Post-Verification - Rawlette, Sharon Hewitt (Journal of Scientific Exploration, 2019)
Many people are persuaded of the existence of psychic phenomena by their own spontaneous experiences of apparent psi. However, without some measure of how often psi-suggestive experiences can be expected to occur purely by chance, it is difficult to determine the epistemic import of these cases. While methods have been developed to find statistical baselines for some spontaneous cases—specifically, ones in which cases of interest can be identified before any verification of their supposedly psychic content has been obtained—many spontaneous cases of purported psi are not identified as such until after some degree of spontaneous verification occurs: for instance, when a person notices a striking correspondence between their mental state and another event to which that state appears to have no physical causal connection. This paper develops a method applicable to these cases—the time-slice method for calculating baseline correspondence potential—and thus enables individuals to determine the epistemic import of their own spontaneous psi experiences.